Natalidad de Chelydra serpentina (Testudines: Chelydridae) en Costa Rica - Pitty Flausín, Lety (1996)
Three Chelydra serpentina nests were monitored from September through October 1993. Maximum natality was 92% (mean 33.73%) and seemed to be associated with high temperature potasium and a moderate concentration of calcium in the soil. Nests were located at less than 80 m from water and soil characteristics were: 21.8-22.9 oC, c1ay-loam texture penetrabilily indcx 0.27·0.87 kg/cm2, humidity 48- 74 %.